The Effectiveness of Climate Change Litigation as a Venue to Uphold State Climate Change Obligations in Indonesia - Ariani, Deniza (UI Scholars Hub, 2019)
Climate change has increasingly raised concerns regarding the continuity of human life. As a consequence, there are certain obligations upon governments to conduct climate change mitigation and adaptation measures. However, there remains the issue of ensuring States comply with their obligations. Under the Paris Agreement, a recent international legal instrument concerning climate change, compliance is one of the matters addressed. The Agreement introduces a “Compliance Committee”. The Agreement, however, underlines that the Compliance Committee’s actions will be limited to non-adversarial and non-punitive measures. Therefore, it remains unclear whether non-compliant States would indeed adhere to the Compliance Committee. Recently, climate change litigation has begun to develop around the world. This form of litigation also encompasses lawsuits from citizens against States, concerning such State’s obligations in mitigating and adapting to climate change. With such development, a question arises, which is “How effective can climate change litigation be in upholding Indonesia’s climate change obligations?” In answering such question, this research will use the normative juridical method, consisting primarily of bibliographical research. The composition of this research will firstly consist of an explanation of the research background, including an explanation on current State climate change obligations, which leads to the main research problem, and a comparison with prior research. Next, an analysis upon recent developments in Indonesia, along with a brief comparison with global developments will be conducted, which will then be used in answering the research problem. The paper will then conclude with conclusions and suggestions.